Biochemical characterization of pectinase activity from the digestive midgut fluid of larvae and adult of the Colorado potato beetle, Leptinotarsa decemlineata (Col: Chrysomelidae) - Razieh Karimi; Majid Kazzazi; Mohammad Vatanparast (Arthropods, 2015)
The study of pectinase enzyme in potato leaf beetle that is the most important pest of potatoes consider as an effective way to develop control methods because this enzyme is important in degrading plant cell wall. Pectinase enzyme was studied in midgut of Colorado potato beetle (CPB). This enzyme was extracted from the midgut of larvae and adult of CPB and then their important features were examined by specific substrate, pectin 1 percent. The optimum enzyme activity in 4th instar larvae and adult occurred at pH 5-6 range. Effect of temperature on enzyme activity were examined, the results suggest that the pectinase in midgut of 4th instar larvae and adult shows maximum activity at temperature 40 Celsius degree and 35 Celsius degree, respectively. Zymogram analysis showed presence of two activity bands for pectinase enzyme. The effect of various chemical compounds on the activity of enzyme showed that SDS, Urea and Tris reduced the enzyme activity. NaCl and CaCl2 increased this enzyme activity in 4th instar larvae and adult of CPB. This is first report of pectinase activity in L. decemlineata.